Removal of formaldehyde from overactivated‐carbon‐fiber‐loaded biological enzyme. Issue 4 (30th May 2013) - Zuo, Hongmei; Zhang, Hua; Zhang, Xingxiang; Han, Na
<x xml:space="preserve">Abstract</x> To remove formaldehyde effectively, we used activated carbon fiber as a carrier to prepare the composite materials (biological enzyme/activated carbon fiber) by loading biological enzyme on its surface. A one‐factor‐at‐a‐time design and orthogonal design were used in the experimental design methods to optimize the biological enzyme based on soya protein. The experimental results indicate that the pH value was the most significant condition for optimizing the biological enzyme. The optimum orthogonal design conditions were proposed to be a reaction temperature of 80°C, a pH of 4, a reaction time of 6 h, and an amino nitrogen content of up to 5.4%. In addition, the morphologies of the composite materials were characterized with scanning electron microscopy, and the removal efficiency of formaldehyde was investigated with the acetyl acetone method. The results show that the formaldehyde removal efficiency was the best and the removal rate was 80% when the loading time was 8 h. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 2619–2623, 2013